Aphasia: from Antiquity to the 20th century (Research, Society and Development, 2020)
Aphasia is an acquired impairment of language resulting from a focal brain injury in the language-dominant hemisphere that affects the person's communicative and social functioning and quality of life. The aim of this study was to carry out a narrative review on the historical discoveries in aphasiology, highlighting the main theorists and studies until the 20th century. The information was consulted in books, in the databases available on the CAPES Portal of e-Journals, and, in addition, Google Scholar. The understanding of aphasia as a language disorder started in the Old Age. In the 19th century, the issue of functional localization dominated the study of the relationship between language and brain. In the 20th century, the focus slowly shifted to psycholinguistically formulated models of language production and understanding.